1993
DOI: 10.1542/peds.91.5.880
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Progression to Severe Obesity in a Group of Obese Schoolchildren Treated With Family Therapy

Abstract: Study objective. To evaluate the effect of family therapy on childhood obesity. Design. Clinical trial. One year follow-up. Setting. Referral from school after screening. Participants. Of 1774 children (aged 10 to 11), screened for obesity, 44 obese children were divided into two treatment groups. In an untreated control group of 50 obese children, screened in the same manner, body mass index (BMI) values were recorded twice, at 10 to 11 and at 14 years of age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…In programs developed by Golan, Weizman, Apter, and Fainaru (1998), parents were viewed as the “exclusive agents of change.” This focus on parents highlights parenting skill as the target of intervention: “Approaching parents exclusively shifts the focus of the group from weight issues to parenting issues” (Golan & Crow, 2004a, p. 45). Finally, family therapy was used by Flodmark, Ohlsson, Ryden, and Sveger (1993) to strengthen hierarchies, reduce blurred boundaries and coalitions, and reinforce resources for coping in families of obese children…”
Section: Family-based Interventions For Childhood Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…In programs developed by Golan, Weizman, Apter, and Fainaru (1998), parents were viewed as the “exclusive agents of change.” This focus on parents highlights parenting skill as the target of intervention: “Approaching parents exclusively shifts the focus of the group from weight issues to parenting issues” (Golan & Crow, 2004a, p. 45). Finally, family therapy was used by Flodmark, Ohlsson, Ryden, and Sveger (1993) to strengthen hierarchies, reduce blurred boundaries and coalitions, and reinforce resources for coping in families of obese children…”
Section: Family-based Interventions For Childhood Obesitymentioning
confidence: 99%
“…In traditional family-based behavior modification programs, there was no benefit associated with adding a parent training component (Aragona et al, 1975; Israel et al, 1994). Golan, Weizman, et al (1998) found clear advantages when parents were made the exclusive agents of change (relative to treatment in which the child was the exclusive agent of change), and Flodmark et al (1993) found significant advantages associ- ated with family therapy (relative to dietary counseling and pediatrician visits).…”
Section: Family-based Interventions For Childhood Obesitymentioning
confidence: 99%
“…The program also included 90 min of physical activity twice a week for the adolescents. The parents' program consisted of nutrition-related topics and systemic interventions to facilitate family functioning by reinforcing family resources and improv-ing the emotional climate for adolescents with obesity (Flodmark et al, 1993).…”
Section: Description Of the Family-based Behavioral Programmentioning
confidence: 99%
“…Guidelines for obesity interventions in children and adolescents recommend comprehensive treatments combining dietary intervention, behavioral approaches, and physical activities, which have shown to have beneficial effects on adiposity (Hoelscher, Kirk, Ritchie, & Cunningham-Sabo, 2013; Luttikhuis et al, 2009; Whitlock, O’Connor, Williams, Beil, & Lutz, 2010). Targeting parents is also an important component of the treatment and family-based programs have been widely developed (Epstein, Valoski, Koeske, & Wing, 1986; Epstein, Valoski, Wing, & McCurley, 1994; Flodmark, Ohlsson, Rydén, & Sveger, 1993; Golan, Weizman, Apter, & Fainaru, 1998; Golley, Magarey, Baur, Steinbeck, & Daniels, 2007; Ho et al, 2012; Kitzmann et al, 2010; Sung-Chan, Sung, Zhao, & Brownson, 2013; Tanas, Marcolongo, Pedretti, & Gilli, 2007). Most of these programs have involved work on improving parental modeling and positive parenting styles, such as child-management strategies and authoritative parenting.…”
mentioning
confidence: 99%
“…The latter may include a past or current eating disorder or difficulty with attachment and nurturing. The application of family systems theory to understanding obesity in childhood is a promising but largely unexplored research and clinical area (Flodmark, Ohlsson, Ryden, & Sveger, 1993). The basic premise, that obesity occurs within the context of specific family structures and patterns and can serve both homeostatic and conflict avoidance purposes, is ripe for investigation.…”
Section: Obesity In Childhood: Consensus Findingsmentioning
confidence: 99%